2017
DOI: 10.1108/ijcthr-09-2015-0117
|View full text |Cite
|
Sign up to set email alerts
|

Choice overload in holiday destination choices

Abstract: Purpose This research aims to investigates whether and why choice overload (CO) occurs when people select a vacation destination. Design/methodology/approach This is a two-group (large choice-set vs small choice-set) between-subject factorial design. Dependent variables representing CO-effects are post-choice satisfaction and regret. Choice confusion and choice uncertainty are mediators. Findings Relative to people choosing from a small destination portfolio, people who choose from a large portfolio are le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 58 publications
2
29
1
Order By: Relevance
“…As a result, when faced with more products, participants experienced more negative effects on attraction and desire to make a choice. In addition to choosing tangible consumer goods, recent studies on dating partner (D’Angelo and Toma 2017 ), vacation destination (Thai and Yuksel 2017 ) and electricity service provider (Jilke et al 2016 ) selections also found greater dissatisfaction and regret when decisions were made in a hyperchoice relative to a simple-choice condition.…”
Section: Mixed Results Of Hyperchoicementioning
confidence: 99%
See 1 more Smart Citation
“…As a result, when faced with more products, participants experienced more negative effects on attraction and desire to make a choice. In addition to choosing tangible consumer goods, recent studies on dating partner (D’Angelo and Toma 2017 ), vacation destination (Thai and Yuksel 2017 ) and electricity service provider (Jilke et al 2016 ) selections also found greater dissatisfaction and regret when decisions were made in a hyperchoice relative to a simple-choice condition.…”
Section: Mixed Results Of Hyperchoicementioning
confidence: 99%
“…One strategy, as adopted by the wholesale giant Costco or the global discount supermarket ALDI, is to limit product selection. This strategy was echoed in a study on holiday destination choice (Thai and Yuksel 2017 ). The authors suggested travel agencies use a screening tool to narrow down the range of options and present a customized portfolio.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al, 2015), budget accommodation services (S. Yang et al, 2017), eco-friendly accommodations (Zanon & Teichmann, 2016), holiday destination choices (Thai & Yuksel, 2017), theme factors (Åstrøm, 2017), and customer co-creation and adoption (Sarmah et al, 2017). However, scant research has reported on the price determinants of the non–hotel room offers (Monty & Skidmore, 2003; Portolan, 2013; D.…”
Section: Theoretical Background and Literature Surveymentioning
confidence: 99%
“…Rosen's model considers the presence of a range of goods from which individuals select the necessary attributes. During the past two decades, there has been an increase in applications of hedonic pricing models in various tourism research reports-for example, sun and beach package tours (Thrane, 2005), service quality (C. Lu et al, 2015), budget accommodation services (S. Yang et al, 2017), eco-friendly accommodations (Zanon & Teichmann, 2016), holiday destination choices (Thai & Yuksel, 2017), theme factors (Åstrøm, 2017), and customer co-creation and adoption (Sarmah et al, 2017). However, scant research has reported on the price determinants of the non-hotel room offers (Monty & Skidmore, 2003;Portolan, 2013;D.…”
Section: Theoretical Background and Literature Surveymentioning
confidence: 99%
“…Choosing between hotels: impact of bimodal rating summary… Choice complexity is a major problem in tourism and hospitality. Most businesses within the industry tend to offer large varieties of (online and offline) products and services, and allow for high levels of customization of already complicated (multiple events and/or multidestinations) product-service bundles (Park and Jang 2013;Thai and Yuksel 2017). Sometimes, the customer's choice behavior in such complicated settings is still understood in terms of rational utility maximization (de Oliveira Santos et al 2011).…”
mentioning
confidence: 99%